2009
DOI: 10.1080/02652030802425334
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate content of lettuce (Lactuca sativaL.) after fertilization with sewage sludge and irrigation with treated wastewater

Abstract: A romaine-type lettuce (Lactuca sativa L.) was cultivated over three crop seasons (spring 2005, spring 2006 and autumn-winter 2006) in six 36 m(2) plots in Alcázar de San Juan, Spain. A drip irrigation system was used to water all plots: five plots with drinking water and one plot with wastewater from the activated sludge system of a wastewater treatment plant (WWTP). One drinking water-irrigated plot was not fertilized (control). Five different treatments were applied to the soil: three organic mixtures (sewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…Data from a recent experiment on plant growth rates in a multi-loop aquaponic system (Goddek & Vermeulen 2017) was used to derive the nitrate uptake of the lettuce (Table 7.3). The uptake observations were consistent with the ones reported by Castro et al (2009) and Mathieu et al (2006). The formula for sizing one-loop aquaponic systems according to given rule of thumb is:…”
Section: Recirculating Aquaculture Systemsupporting
confidence: 89%
“…Data from a recent experiment on plant growth rates in a multi-loop aquaponic system (Goddek & Vermeulen 2017) was used to derive the nitrate uptake of the lettuce (Table 7.3). The uptake observations were consistent with the ones reported by Castro et al (2009) and Mathieu et al (2006). The formula for sizing one-loop aquaponic systems according to given rule of thumb is:…”
Section: Recirculating Aquaculture Systemsupporting
confidence: 89%
“…Since in lettuce L. sativa, protected or open grown, harvested in the period from October 1 to March 31 the limit amount of nitrates is 4,500 ppm expressed on the fresh weight basis, Bio-algeen S-90 or Megagreen are obviously great treatments for nitrate-related toxicity reduction of lettuce. Compared to the sewage sludge used by Castro et al (2009), and mineral (94% Ca(NO 3 ) 2 + 6% NH 4 NO 3 ) and organic (biostabilised compost) fertilizers used by Premuzic et al (2001), in terms of nitrate concentration, Megagreen fertilizer would be a better choice for lettuce production.…”
Section: Discussionmentioning
confidence: 97%
“…As far as we know, the possible application of these two preparations in the winter production of leafy vegetables, including lettuce has not been tested so far. As for the production of lettuce, it has been proven that organic fertilizers are more suitable than inorganic ones in lettuce cultivation in river sand (Masarirambi et al 2010), that toxic nitrate concentration in romaine-type lettuce increases after fertilization with sewage sludge (Castro et al 2009), and that mineral fertilization increases the nitrate concentration in the lettuce cultivar Mantecosa (Premuzic et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…3 that the cultivars Thaís and Verônica presented the highest levels of nitrate and the latter did not differ statically from the Vanda cultivar. Castro et al (2009) compared the nitrate levels of lettuce leaves and reported higer nitrate levels compared to this study, possibly due to nitrate concentration in the vegetal tissues occurred through using sewage sludge. As for the isolated effect of the solutions (Fig.…”
Section: Source Of Variation Gfmentioning
confidence: 44%